THE LIMBIC SYSTEM IN ADULT HUMAN BRAINS – COMPARATIVE MORPHOMETRIC ANATOMO-IMAGISTIC STUDY - Alin Horatiu Nedelcu; David-Constantin Bulgaru; Simona Alice Partene Vicoleanu; Razvan Tudor Tepordei; Cosmin Gabriel Popa; Roxana-Andreea Popa; Marius Constantin Moraru; Manuela Ursaru (Romanian Journal of Oral Rehabilitation)
The limbic system is made up of a vast network of components such as the cingulate gyrus, the hippocampus and the parahippocampus or ismic formation. All these components make up the “Great Lobe Limbic”. Through its components, it makes numerous connections such as those with the septal area, the thalamus, the hypothalamus, the habenular nuclei or the mammary bodies. Our study aims to demonstrate the variability of the components of the limbic system through their morphometric evaluation on anatomical parts and, respectively on CT images. 13 adult brains without known neurological abnormalities, fixed in 10% formalin solution for a minimum of 10 weeks, and 22 CT craniocerebral datasets of patients without any organic cerebral dysfunctions were evaluated. To remove any bias, two teams of two investors each performed examinations. The anterior, superior and posterior diameters of the cingulate gyrus were measured, as well as the longitudinal and transverse diameters of the parahippocampal and isthmic gyri. In order to be able to compare the measurements made on the anatomical preparations with those provided by the CT images, we reported the diameters mentioned with the diameters of the corresponding hemisphere. All statistical analyses were conducted using Microsoft Excell 2016. Linear data were evaluated as mean +/- standard deviation. Comparisons between continuous variables were performed using the Student t-test. Statistical significance was set at a P-value < 0.05. Statistical analyses demonstrated significant differences (p < 0.01) between the two groups regarding FL/ACG, SL/SCG, OL/PCG and LCI/TCI. Only the LPG/TPG ratio was similar between the two cohorts. The limbic system has a great morphological and morphometrically variability. Our morphometric study proved precisely the variability that is found, both on anatomical parts and on CT images.